Long-term Development of Small-scale Industries in Relation to Economic Development: Looking for General Propositions (The Pakistan Development Review, 1994)
The growing attention, in literature on economic development, towards the role of Small-scale Industries (SSls) within the economy of the less developed countries (LDCs), is strongly associated with the recognised current economic and social problems of continuing imbalance in the labour market leading to high unemployment rates, the persistence of large intra- and inter-regional socio-economic inequalities; and the consolidation of extremely concentrated patterns of urbanisation, facing these countries. On the other hand, there is the notion stating that the importance of SSls decreases with the course of economic development. The available empirical evidence on this issue diverges significantly from the afore-mentioned notion. In the background of this contradictory evidence, the paper aimed to discuss this issue and arrive at some general conclusions which would help in deriving a pattern from the available studies and evidence on the issue under reference. The conclusion of the paper suggests that no matter how far a country has developed, but as long as domestic problems of high rates of unemployment, mass poverty or unequal distribution of income exist, SSls will continue to play an important role as a 'last resort' for the poor of the country.